Pendampingan Digitalisasi Seleksi Tenaga Kerja Berbasis Metode SAW pada PT Qjob Saka Gemilang - Nurul Agami; Leni Novianti; Nurlaili Rahmi (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
PT Qjob Saka Gemilang is a workforce recruitment company specializing in supplying prospective Sales Executives to PT Indosat Ooredoo as its primary partner. The employee selection process at the company was previously conducted manually by the Human Resource Development (HRD) department without a systematic decision-support tool, making the process susceptible to subjective judgment and time-consuming. This community service program aimed to assist PT Qjob Saka Gemilang in adopting a web-based Decision Support System (DSS) implementing the Simple Additive Weighting (SAW) method to facilitate a more objective and efficient evaluation and ranking of job applicants. The program was carried out through several stages, including partner needs assessment, participatory system design involving HRD personnel, application development, and training and mentoring for HRD staff, administrators, and company management. Throughout the mentoring process, the partner demonstrated a significant improvement in its recruitment practices, shifting from manual record-keeping and subjective evaluation to the use of a digital system for determining evaluation criteria, assigning weights, and automatically generating applicant rankings. Functional testing confirmed that all application modules operated according to the system design specifications. The results indicate that mentoring in the implementation of a decision support system can effectively help small and medium-sized enterprises improve the objectivity and efficiency of employee selection processes while supporting sustainable technology adoption